The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.3389/fphar.2019.01457
|View full text |Cite
|
Sign up to set email alerts
|

Long Non-Coding RNA in Drug Resistance of Non-Small Cell Lung Cancer: A Mini Review

Abstract: Lung cancer is one of main causes of cancer mortality and 83% of lung cancer cases are classified as non-small cell lung cancer (NSCLC). Patients with NSCLC usually have a poor prognosis and one of the leading causes is drug resistance. With the progress of drug therapy, the emergence and development of drug resistance affected the prognosis of patients severely. Accumulating evidence reveals that long non-coding RNAs (lncRNAs), as "dark matters" of the human genome, is of great significance to drug resistance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 81 publications
(87 reference statements)
1
14
0
Order By: Relevance
“…However, we detected little variation in the phosphorylated-AKT and -ERK levels by siRNAs anti-SOX2-OT in NCI-H1975 cells. Therefore, our results support the hypothesis that LncRNAs are functional participants in therapy resistance/sensitivity to cancer-drugs, and target-gene therapies "EGFR/AKT/ERK/mTOR"[47]. It has been previously reported that SOX2-OT participates in the activation of the AKT-member of cellular signaling pathways in cholangiocarcinoma[14], as well as being involved in the magnitude of resistance mechanism to EGFR-TKIs-based treatment related to the functionality of phosphatase PTEN, reducing AKT phosphorylation in NSCLC[54].…”
supporting
confidence: 83%
“…However, we detected little variation in the phosphorylated-AKT and -ERK levels by siRNAs anti-SOX2-OT in NCI-H1975 cells. Therefore, our results support the hypothesis that LncRNAs are functional participants in therapy resistance/sensitivity to cancer-drugs, and target-gene therapies "EGFR/AKT/ERK/mTOR"[47]. It has been previously reported that SOX2-OT participates in the activation of the AKT-member of cellular signaling pathways in cholangiocarcinoma[14], as well as being involved in the magnitude of resistance mechanism to EGFR-TKIs-based treatment related to the functionality of phosphatase PTEN, reducing AKT phosphorylation in NSCLC[54].…”
supporting
confidence: 83%
“…4,5 Cisplatin (DDP) is a chemotherapeutic drug widely used in the treatment of lung cancer, but drug resistance of tumors had affected its application. 6 Exploring ways to reverse DDP drug resistance will improve the treatment of lung cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Among these non-coding genes, long non-coding RNAs (lncRNAs) are emerging as a new class of indispensable players involved in the tumorigenesis [ 3 , 5 , 6 ]. Moreover, the dysregulation of a number of lncRNA targets has been reported to associate with the stage and prognosis of many tumor types [ 7 , 8 ] including breast cancer [ 9 , 10 ], lung cancer [ 11 , 12 ], and liver cancer [ 13 , 14 ], as well as linked to resistance against chemotherapy and targeted therapy [ 15 , 16 ]. For example, the overexpression of the lncRNAHOX transcript antisense intergenic RNA(HOTAIR) promotes the metastasis of breast cancer cells [ 17 ].…”
Section: Identifying Lncrnas In Cancermentioning
confidence: 99%